Organisational Culture: A Key to Enhancing Teacher Job Satisfaction at Witthayapanya Matthayom School, Thailand - Rizka Dara Vonna; Nur Hasmalawati (Psikoislamedia: Jurnal Psikologi, 2026)
This study explores the role of organizational culture in shaping teacher job satisfaction at a Muslim school in Thailand within a predominantly non-Muslim society. This context is important because the school functions not only as a formal educational institution but also as a space for preserving religious values and Islamic identity. The study employed a qualitative case study design. Data were collected through in-depth interviews with five teachers selected purposively. The findings reveal that organizational culture characterised by religious values, togetherness, and mutual respect contributes to teacher job satisfaction. Teachers felt motivated and emotionally connected to the school when organizational culture aligned with their personal and spiritual values. Ikhlas (sincerity) emerged as a key spiritual value underlying teachers’ commitment. Supportive leadership and a harmonious working environment further strengthened teachers’ sense of belonging. These findings highlight the importance of organizational culture in faith-based schools operating in minority contexts.